Transmission model of dengue virus by Aedes aegypti and Aedes albopictus - Sungchasit, R.; Pongsumpun, P.; Tang, I. M. (My University, 2013)
Mathematical models are used for describing many diseases. Dengue disease is occurred by biting of infected Aedes aegypti and Aedes albopictus mosquitoes. Dengue outbreak is found during the rainy season. Each Aedes mosquito has the different dengue outbreaks and they depend on the temperature and areas. The standard dynamical modeling method is used in this study. The SIR (susceptible-infectedrecovered) model is modified to describe the transmission of dengue virus by two species of vectors. The transmission of dengue virus is varied with time. The dynamical analysis method is used for analyzing this model. We confirm these results by using numerical results. © 2013 Pushpa Publishing House, Allahabad, India.
Keywords: Aedes aegypti; Aedes albopictus; Dengue disease; Equilibrium points; Local stability; Mathematical modeling